High-quality perovskite films via post-annealing microwave treatment. (10th April 2019) - Wang, Kai-Li; Zhang, Cong-Cong; Jiang, Yu-Rong; Liu, Hai-Rui; Li, Xiao-Mei; Jain, Sagar M.; Ma, Heng
Abstract : The crystalline quality of the perovskite film plays a key role in improving the optoelectronic properties and the performance of planar perovskite hybrid solar cells (PSCs). Abstract : The crystalline quality of the perovskite film plays a key role in improving the optoelectronic properties and the performance of planar perovskite hybrid solar cells (PSCs). In this study, a methodology employing post-annealing microwave treatment (MPAT) for fine tuning the crystallization of perovskite films is proposed. It was found that the microwave induced electromagnetic waves result in the vibration of dipoles and ions at high frequencies in perovskite crystals, which catalyzes the Ostwald ripening process and results in good quality perovskite films. High quality perovskite films were obtained after being subjected to MPAT with 350 watts of power for 25 seconds. The resulting films, demonstrating an inverted solar cell architecture, and showed a champion efficiency of 13.39%. This was a significant improvement in the performance compared to those of the devices employing films without MPAT treatment (PCE = 11.5%). The MPAT provides a way to prepare high quality perovskite films that are of particular significance for the manufacturing of large area perovskite solar cells.